Individual home and university environment factors as correlates of student attrition in private universities in Nairobi County, Kenya - Njoroge, Mary Mukami (Strathmore University, 2017)
Completion of university education within prescribed time limits has been a concern of universities for decades. As governments emphasize that institutions of higher learning churn out an educated work force, relevant information is required by the universities to curb student attrition. The purpose of this study was to investigate the relationship between selected individual, home and university environmental factors and students ' attrition in private universities in Nairobi County, Kenya and further establish current student attrition levels in private universities in Nairobi. The target population was 24901 second year students in private universities. Stratified sampling was used to select the 387 students for the study. In addition purposive sampling was used to select nine faculty members. Sixty (60) university dropouts were identified through the snowballing method. Data was collected using se lf-administered questionnaires for the second year students and interview guide for university staff. Data for sixty university dropout s was collected telephonically. Structural Equation Modeling (SEM) and Pearson Product Moment Correlation Coefficient were used to test the relationships between the independent variables (individual, home and university environmental factors) and the dependent variable, student Attrition. Initially, preliminary and descriptive statistical analyses were performed. This included analysis of demographic data and analysis of examination retakes, semester deferments and student drop out. Data study was analyzed using maximum likelihood estimates (MLE). The findings established current student attrition levels of thirty seven per cent (37%). From the results student attrition was found to be correlated to peer support, parental support and student faculty interaction. The study recommends the need for interventions, such as establishment of constant student lecturer interactions and provision of adequate facilities to create a conducive environment for study. Also, strategies that will encourage peer interaction should be developed as well as adequate financial support to students by parents and government actors. All these will enhance peer support and increased emphasis on faculty interaction through availing time and space by university management thereby reducing student attrition.
Submitted in total fulfillment of the requirements for the degree of Doctor of Philosophy in Educational Psychology at Strathmore University
Keywords: Student Attrition; University Education; Home and University Environment